2021
DOI: 10.1186/s13063-021-05053-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailable turmeric extract for knee osteoarthritis: a randomized, non-inferiority trial versus paracetamol

Abstract: Background To compare the efficacy and safety of bioavailable turmeric extract versus paracetamol in patients with knee osteoarthritis (OA). Methods In this randomized, non-inferiority, controlled clinical study, patients of knee OA were randomized to receive bioavailable turmeric extract (BCM-95®) 500 mg capsule two times daily or paracetamol 650 mg tablet three times daily for 6 weeks. The primary outcome measure was Western Ontario and McMaster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
0
27
0
6
Order By: Relevance
“…In a comparative study with the NSAID, diclofenac, 4 weeks of curcumin supplementation lowered the secretion of COX-2 by monocytes in synovial fluid at similar levels to diclofenac [ 39 ]. In another comparative drug trial, 8-weeks of curcumin supplementation reduced concentrations of CRP and TNF-α, whereas paracetamol administration did not affect these markers [ 40 ]. However, in another OA study, compared to the placebo, 6 weeks of curcumin supplementation did not significantly alter the ESR or concentrations of IL-4, IL-6, CRP, TNF-α [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study with the NSAID, diclofenac, 4 weeks of curcumin supplementation lowered the secretion of COX-2 by monocytes in synovial fluid at similar levels to diclofenac [ 39 ]. In another comparative drug trial, 8-weeks of curcumin supplementation reduced concentrations of CRP and TNF-α, whereas paracetamol administration did not affect these markers [ 40 ]. However, in another OA study, compared to the placebo, 6 weeks of curcumin supplementation did not significantly alter the ESR or concentrations of IL-4, IL-6, CRP, TNF-α [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two clinical trials assessed the effectiveness of a curcumin-essential oil complex in the management of knee OA compared to common drugs, such as diclofenac or paracetamol. Together, these studies revealed that co-administration of 500 mg of BCM-95 ® CG plus 50 mg of diclofenac twice a day (group 1, 71 patients) compared to administration of 50 mg of diclofenac twice a day alone (group 2, 69 patients), as well as the administration of 500 mg of BCM-95 ® CG twice a day (73 patients) or 650 mg of paracetamol three times a day (71 patients), not only significantly improved knee OA symptoms, but reduced the gastrointestinal (GI) side effects related to NSAIDs treatment and the need of other analgesics, thus suggesting a good alternative treatment option [79,80]. Control: unformulated curcumin; ND: not detected; AUC: area under the drug concentration-time curve; NA: not applicable; a mean ± standard error of mean; b mean; c mean ± standard deviation; d no reported standard deviation or error; e results in mg/mL; 1 AUC 0-3 ; 2 AUC 0-6 ; 3 AUC 0-8 ; 4 AUC 0-12 ; 5 AUC 0-24 ; 6 AUC 0-48 ; 7 AUC 0-∞ .…”
Section: The Early Factors Impacting Metabolismmentioning
confidence: 99%
“…According to the World Health Organization (WHO), it is projected that approximately more than 130 million will be affected by OA, and more than 40 million people will be severely disabled by the disease. 7 This is also because of the medical advances that are increasing the average life expectancy. 8 Women have a higher prevalence of OA than men.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Women have a higher prevalence of OA than men. 7 Osteoarthritis, especially knee OA, has been proven to impair the physical functions and worsens the overall quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation